Educator Characteristics in Islamic Tradition and Modern Law: Insights From Hadith - Alfiah Alfiah; Rahman Rahman; Lailiyatun Nafisah; Yuliharti Yuliharti; Zikri Darussamin; Siti Nuri Nurhaidah; Wasalmi Wasalmi (Pascasarjana Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2024)
This article aims to explore the characteristics of educators depicted in the Hadith of the Prophet. Educators in this era are faced with various challenges, which require them to have strong qualities in order to guide students according to the provisions of Allah SWT. This research uses a descriptive qualitative approach through the literature study method. The research results show that the ideal characteristics of educators in the hadith involve the presence of deep compassion in the process of educating students, justice, a democratic approach, and dedication to providing motivation and clarity in conveying knowledge to those who need it. Through the application of these characteristics, it is hoped that the goal of education can be achieved, namely developing the potential of students so that they become individuals who are faithful, knowledgeable, creative, independent, and can become democratic and responsible citizens. Keywords:Characteristics, Educators, Hadith, Law no. 20 of 2003